To Assess The Knowledge Of Nurses Regarding Enteral Nutrition In Neuro Intensive Care Unit In Patiala - Minhas, Sonia; Neha, Neha; Yadav, Ran Vijay; Deepansha, Deepansha; Alisha, Alisha; Verma, Nishakant (Journal of Neonatal Surgery, 2025)
Background: Nurses play a major role in initiation and management of EN and monitoring of potential complication. The role of EN is very significant in neurology and neurosurgery patients, who are critically ill and are dependent on EN for longer duration of time. Malnutrition is very common problem among neurointensive care unit patients. It is unclear whether neuro intensive care nurses have adequate knowledge regarding EN. Therefore aim of this study is to assess the neurointensive care nurses knowledge regarding EN. Methods: A descriptive cross-sectional sectional study was conducted in November 2020 in Patiala Punjab. Random sampling method was used and ICU nurses from different private hospitals participated in the study. A self-administered 15 item questionnaire related to ICU nurses knowledge about EN was used to collect the data. Result: Out of 100 participants 87% were females and 13% were males 44% of the participants were aged between 26 -30 years and 41% of the nurses were between the age group of 20-25 years. Most of the Participants (34%) had 0-2 years of working experience as nurse. Total of 57% of the nurses had not attended any EN training and 32% of the participants were not aware of availability of EN protocol in the hospital. Only 5% participants had adequate knowledge about EN and 41% had inadequate knowledge regarding EN. There was no association between level of nurses knowledge regarding EN and the level of education. Conclusion: A significant gap was identified in neurointensive care nurses knowledge regarding EN. This indicates that there is need to upgrade and refresh nurses knowledge regarding EN by training program.